Technical Report on Development of USES Specific Aptitude Test Battery for Ward Clerk (medical ser.) 219.388 - Manpower Administration (DOL), Washington, DC.; Manpower Administration (DOL), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Research which resulted in the development of the Specific Aptitude Test Battery for use in selecting inexperienced or untrained individuals for training as ward clerks is described. Occupational norms in terms of minimum qualifying scores for the aptitude measures which predict job performance were established. The General Aptitude Test Battery and a descriptive rating scale completed by supervisors were administered to 5 males and 180 females employed as ward clerks by various hospitals throughout the country. Final norms were derived on the basis of a comparison of the degree to which trial norms consisting of various combinations of aptitudes, at trial cutting scores, differentiated between 64 percent of the sample considered to be good workers and 36 percent considered to be poor workers. Cutting scores of 75 in general learning ability, 75 in numerical aptitude, 95 in clerical perception, and 85 in motor coordination provided the best standard of evaluation. Statistical data, names of hospitals participating, job description, and supervisor's rating scale are included. (SM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aptitude Tests; Employment Qualifications; Hospital Personnel; Job Analysis; Occupational Information; Personnel Evaluation; Statistical Analysis; Test Validity; General Aptitude Test Battery; Reports, Research